Participatory Action Research in the Implementing Process of Evidence-Based Intervention to Prevent Childhood Obesity: Project Design of the “Healthy Future” Study - Gudbjørg Øen; Kjell Morten Stormark (Journal of Obesity)
Objective. To describe the design of the developmental project Healthy Future that aims to implement a new evidence-based program for the prevention of childhood obesity and collaboration and sharing of work between specialist and community health care professionals in parts of a county in western Norway. Methods. Comprehensive participatory planning and evaluation (CPPE) process as an action-oriented research approach was chosen, using mixed data sources, mixed methods, and triangulation. Discussion. A bottom-up approach might decrease the barriers when new evidence-based childhood prevention interventions are going to be implemented. It is crucial not only to build partnership and shared understanding, motivation, and vision, but also to consider the frames of the organizations, such as competencies, and time to carry out the interventions at the right level of health care service and adapt to the overweight children and their families needs. Conclusion. The developmental process of new health care programs is complex and multileveled and requires a framework to guide the process. By CPPE approach evidence-based health care practice can be delivered based on research, user knowledge, and provider knowledge in the field of childhood overweight and obesity in a certain context.